Development of Characterization Platform Dedicated to Bio-Inspired Objects at the Nanoscale. (4th May 2016) - Carmignani, Corentin; Thuaire, Aurélie; Rongier, Anaelle; Altamura, Lucie; Brun, Christophe; Reynaud, Patrick; Rolland, Emmanuel; David, Nadine; Rannou, Patrice; Forge, Vincent; Ernst, Thomas; Cheramy, Séverine
Abstract : Based on their nanoscale size and morphology, as well as on their auto-assembling properties, bio-inspired nano-objects have been identified as potential interconnection and sensor materials. Their electrical properties, namely conduction mechanism and electrical contact, have to be studied in order to enable a comparison with standard microelectronic components. In this paper, a generic characterization platform for bio-inspired nano-objects is proposed, enabling electrical investigations ranging from dry electrical measurements to wet electrochemical investigation, and for bio-inspired materials morphologies from single nanowires to films. Various electrode patterns have been designed and fabricated on 200mm silicon substrates, before being diced at chip scale and embedded in easy-to-plug systems for dry and wet measurements, including climatic chamber or glove box. Fully biocompatible microelectronic fabrication processes have been selected.